2013
DOI: 10.1371/journal.pone.0082387
|View full text |Cite
|
Sign up to set email alerts
|

Re-Visiting Insecticide Resistance Status in Anopheles gambiae from Côte d'Ivoire: A Nation-Wide Informative Survey

Abstract: Insecticide resistance constitutes a major threat that may undermine current gain in malaria control in most endemic countries. National Malaria Control Programmes (NMCPs) need as much information as possible on the resistance status of malaria vectors and underlying mechanisms in order to implement the most relevant and efficient control strategy. Bioassays, biochemical and molecular analysis were performed on An. gambiae collected in six sentinel sites in Côte d'Ivoire. The sites were selected on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…Consistent with recent studies carried out in the Korhogo area [6,25], we found very high frequencies of the kdr mutation in the An. gambiae complex population during the four surveys.…”
Section: Frequencies Of the Kdr And Ace-1 Allelessupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with recent studies carried out in the Korhogo area [6,25], we found very high frequencies of the kdr mutation in the An. gambiae complex population during the four surveys.…”
Section: Frequencies Of the Kdr And Ace-1 Allelessupporting
confidence: 93%
“…Consequently, the effectiveness of LLINs may depend on parameters such as the susceptibility of vectors to insecticides and their biting behavior. Unfortunately, resistance to the four insecticide classes used for public health (pyrethroids, organochlorines, carbamates, and organophosphates) is common in the main malaria vector species across Côte d'Ivoire [6,24,37,43]. This resistance involves multiple mechanisms such as metabolic and target site resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquito nets are treated with pyrethroids alone. Of the recent, incorporation of PBO on the LLNs has shown to increase the efficacy of the LLINs against resistant wild populations of mosquitoes [69,70]. Currently, multiple resistance interested in pyrethroid throughout the country against different vector species threatens the use of LLINs to remain as physical barrier only [68,70].…”
Section: Llins Indoor Residual Spraymentioning
confidence: 99%
“…Resistance was monitored only one time in Man [9] and Abengourou [9], respectively; two times in Yamoussoukro [9,10] and San Pedro [9,11] and four times in Abidjan [9,10,12,13] and five times in Korhogo [9,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%